Penerapan Pembelajaran E-Learning Berbasis Moodle Pada Mata Pelajaran Simulasi Digital - Yogi Pangestu; Raja Sakti Arief Daulay (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
There is no e-learning at SMK Al-Washliyah 4, this study aims to produce a learning system that is flexible and in accordance with the times by using moodle-based e-learning learning media. The benefit of this research is to facilitate students and teachers in carrying out teaching and learning. This research uses the Rapid Application Development (RAD) Software Development method. After researchers made observations at school, what schools need now is learning media that can enable teachers and students to carry out teaching and learning activities without being hindered by space and time. After observing, designing, and implementing Moddle-based E-Learning at SMK Al-Washliyah 4, it can be concluded that E-Learning that is made based on Moodle and contains some teacher and student data can have a good impact in providing material, assignments, quizzes, etc. become a very useful learning media for students. teachers because there is no E-learning in schools yet.